2012
DOI: 10.1183/09031936.00033812
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis reveals 12q13.3–q14.1 as new risk locus for sarcoidosis

Abstract: Sarcoidosis is a systemic inflammatory disease of unknown aetiology, influenced by genetic and environmental factors. However, the loci so far identified for sarcoidosis explain only a part of its assumed heritability.To identify further susceptibility loci, we performed a genome-wide association analysis using the Affymetrix 6.0 Human GeneChip followed by validation and replication stages.After quality control, 637 cases, 1233 controls and 677 619 single-nucleotide polymorphisms (SNPs) were available for an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 69 publications
2
21
0
1
Order By: Relevance
“…An independent susceptibility locus was also identified at 12q13.3-q14.1 with the Osteosarcoma amplified 9 (OS9) representing the most likely candidate risk factor. This association has been validated in an independent German population and replicated by a meta-analysis of three independent cohorts of sarcoidosis patients from Germany, Czech Republic and Sweden 74. Data analysis stratified by disease course revealed a stronger association of the lead SNP rs1050045 with acute sarcoidosis.…”
Section: Scanning the Genomementioning
confidence: 62%
“…An independent susceptibility locus was also identified at 12q13.3-q14.1 with the Osteosarcoma amplified 9 (OS9) representing the most likely candidate risk factor. This association has been validated in an independent German population and replicated by a meta-analysis of three independent cohorts of sarcoidosis patients from Germany, Czech Republic and Sweden 74. Data analysis stratified by disease course revealed a stronger association of the lead SNP rs1050045 with acute sarcoidosis.…”
Section: Scanning the Genomementioning
confidence: 62%
“…17 Misfolding and aggregation of serum amyloid A (SAA) might play an important role in sarcoidosis. 17 Misfolding and aggregation of serum amyloid A (SAA) might play an important role in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantigens may derive from misfolded proteins that are insufficiently cleared. It could be demonstrated that single-nucleotide polymorphisms in the OS9 [21] and RAB23 [22] genes are associated with an increased risk of sarcoidosis. Both genes are assumed to be involved in the regulation of the degradation of misfolded proteins or the generation of autophagosomes.…”
mentioning
confidence: 99%